Identification and prevalence of ectoparasites in vannamei shrimp (Litopenaeus vannamei) in Pantai Gading Village, Secanggang District, Langkat Regency - Sumiati, Sumiati; Rosmaiti, Rosmaiti; Komariyah, Siti (Acta Aquatica: Aquatic Sciences Journal, 2022)
Vannamei shrimp (Litopenaeus vannamei) is a type of shrimp that is often cultivated. This study aims to identify ectoparasites and their prevalence in vannamei shrimp in the village of Pantai Gading, Kec. Secanggang Kab. Langkat. This research method is a survey method, where the observed ponds are 3 ponds and samples are taken as much as 5% of the stocking density of biota. Samples were taken randomly and then examined at the Laboratory of the Faculty of Agriculture, Universitas Samudra. Organs observed included carapace, gills, swimming legs, walking legs, and tail. Based on the identification results, three types of ectoparasites that infested were obtained, namely from the Phylum Protozoa including Zoothamnium sp., Epistylis sp. and Vorticella sp., with prevalence of 83.33%, 10% and 7.33%, respectively. The results of the observation of water quality parameters showed that the temperature ranged from 30.7 to 32.3 oC, pH 6.85-7.25, DO 2.6-3.6 mg/l, salinity 7-10 ppt, ammonia 0-0.01 ppm, nitrate 10-12 ppm, and nitrite 0-0.01 ppm. The highest prevalence of ectoparasites is Zoothamnium sp.Keywords: Ectoparasites; Identification; Prevalence; Vannamei Shrimp